Comparative studies on pulsed GTAW and AGTAW on dissimilar alloy C-22 and AISI 316L weldments. (2020) - Advaith, V.; Vaisikan, A.; Thirumalini, S.; Padmanaban, R.; Arivarasu, M.; Ram Prabhu, T.
Abstract: This research article investigates the properties of dissimilar weldments made from the Activated-GTAW and Pulsed GTAW welding techniques. Successful autogenous full penetration weld joints between haste alloy C22 and AISI 316 of 5 mm was achieved by both the welding techniques. The A-GTAW weldments produced full penetration joints with lower heat input than the pulsed GTAW weldments. The characterization of the microstructure of the weldments is achieved using optical, scanning electron microscopes. The tensile, impact, bend and hardness properties are evaluated in the weldments and compared. This article also elucidates the correlation between the microstructure and the properties.